Assessing the Major Industrial Accident Potential Based on Dangerous Substance Criteria: a Framework for Seveso and Non-seveso Facilities - David Javier Castro Rodriguez; Huxiao Shi; Morena Vitale; Micaela Demichela; Antonello A. Barresi (Chemical Engineering Transactions)
In Europe, a major accident is defined as an uncontrolled event like a major emission, fire, or explosion involving dangerous substances, posing immediate or delayed risks to human health and the environment, as stipulated in the Seveso III Directive (2012/18/EU). According to Seveso III, establishments are classified as lower-tier (LTE) and upper-tier (UTE) based on their maximum storage capacity of dangerous substances. Regarding the substance criteria, the European Commission requires notifications of eventual major accidents when at least 5% of the UTE is involved. However, plants outside Seveso III can also meet the previous criteria causing major accidents, even if they are not covered by the safety minimal requirements within the European Directive. This study addresses this limitation by proposing a framework for assessing the potential for major industrial accidents based on dangerous substance criteria, regardless of whether the plant is classified as a Seveso establishment or not. Substance classification and quantification were kept under Annex I of the Seveso III Directive, considering the potential consequences for human health, the environment, and physic-built infrastructure. The dangerousness potential of the hazardous substances was defined based on the consequences of potential scenarios such as toxic releases, energetic events, and large spills. Subsequently, the total index of compliance was determined for each dangerousness category. This index calculates the ratio between stored hazardous substances and their corresponding upper threshold. A linear decisional scale based on the compliance index was established, clustering plants into seven colour zones according to their major accident potentiality and establishing a cutoff point according the 5 % UTE criteria. Anonymized case study data exemplifies this method. This framework improves the assessment of the inherent hazard associated with the stored amounts of dangerous substances, providing a more nuanced method for increase the awareness to major accidents hazard and introducing safety measures in both Seveso and non-Seveso facilities.